Implementation of Good Governance Principles in the Execution of the Waste Collection Fee Policy in Tanjungpinang City in 2024 - Shiwy Wulandari; Yudhanto Satyagraha Adiputra; Eki Darmawan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of good governance principles in the execution of the waste collection fee policy in Tanjungpinang City during 2024, employing an empirical qualitative case study approach. Primary and secondary data were gathered through structured regional regulations, municipal archives, policy documentation, and in-depth interviews with eleven key informants comprising environmental officials, revenue administrators, legislative members, policy analysts, and local taxpayers, alongside direct field observations. The collected empirical material underwent rigorous qualitative analysis through data reduction, data display, and conclusion drawing, with methodological validation achieved via comprehensive source triangulation. The findings indicate that while institutional accountability and informational dissemination channels have been formally established, their operational efficacy remains constrained by inconsistent supervisory reviews and limited public comprehension. Moreover, regulatory enforcement suffers from widespread non-compliance and incomplete taxpayer registration, undermining municipal revenue targets and local fiscal autonomy. The research concludes that optimizing urban environmental governance necessitates strengthening administrative oversight, enhancing interactive communication strategies, and enforcing statutory provisions consistently across all residential and commercial sectors.